Pengaruh Agrikultur Dan Pendapatan Per Kapita Terhadap Penerimaan Pajak Di Negara Sub Sahara Afrika Dengan Kualitas Peraturan Sebagai Pemoderasi - Zulfi, Muhammad Ramadhan; Wijaya, Suparna (PT Wim Solusi Prima, 2023)
This study aims to determine the effect of the agricultural sector and per capita income on tax revenues with the quality of regulations as moderators in Sub-Saharan Africa. This study uses secondary data sourced from the World Bank in Sub-Saharan Africa with a span of 18 years from 2002 to 2019. There are 33 countries that are the object of this research. The research was conducted using panel data regression with the Panel-Corrected Standard Error model. Based on the results of the study, it was found that an increase in the proportion of agricultural sector output to gross domestic product had a negative effect on tax revenues. An increase in per capita income has a positive effect on tax revenues. Improving the quality of regulations has a positive effect on tax revenues. It was found that the moderating variable of regulatory quality strengthens the relationship between agricultural variables and tax revenue variables. This is due to the poor average regulatory quality index in sub-Saharan African countries. Meanwhile, the regulatory quality moderating variable does not affect the relationship between per capita income and tax revenue.